A recursive dynamic computable general equilibrium model - Diao, Xinshen; Thurlow, James (International Food Policy Research Institute, 2012)
The relationship between economic growth and poverty is complex, especially in developing countries where inadequate time series data often makes ex post analysis difficult. This has led to uncertainty over the role of growth in reducing poverty (see, for example, Ravallion 2003; Deaton 2005; Sala-i-Martin and Pinkovskiy 2010). At its core, the growth–poverty relationship is determined by a country’s economic structure, that is, the linkages among sectors, regions, and institutions. It involves macroeconomic considerations, such as fiscal budgets and current accounts, and microlevel decisionmaking of producers and households. It is mediated through (and constrained by) product and factor markets.